Maternal and fetal outcome of severe pre-eclampsia and eclampsia in cesarean section and normal delivery - K, Lokeshwari; B, Sreenivasa (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To evaluate the maternal and fetal outcomes in severe preeclampsia and eclampsia in Cesarean Section and normal delivery . Methods: An observational descriptive study of severe pre-eclampsia-eclampsia conducted in the Department of Obstetrics and Gynaecology, Basaveshwara Medical College Hospital. Gestational age 32-42 weeks were included and imminent deliveries were excluded from the study. Primary outcome variables were mode of delivery, maternal morbidity-mortality, and perinatal morbidity-mortality. Results: 63.2% in severe pre-eclampsia, 50% in eclampsia group delivered vaginally; 15.1% in severe preeclampsia and 25% in eclampsia group underwent elective LSCS; 21.7% in severe preeclampsia and 25% in eclampsia group underwent emergency LSCS. Incidence of cesarean deliveries in severe pre-eclampsia was 36.8% and in eclampsia it was 50%. No maternal death was observed in elective LSCS. Maternal death in vaginal delivery cases was 0.94% in severe preeclampsia and 4.76% in eclampsia. In emergency LSCS cases maternal mortality was 1.4% in severe preeclampsia and 4.76% in eclampsia group. No perinatal mortality was observed in elective LSCS group; 4.7% perinatal mortality occurred in normal delivery, 20.5% in emergency LSCS in severe preeclampsia and 7.1% in eclampsia who were delivered vaginally. Conclusion: In eclampsia, feto-maternal outcome is better in the cesarean deliveries than in the vaginal deliveries